THE STATE SHARE OF TAXES IN THE STATE BUDGET OF THE REPUBLIC OF UZBEKISTAN AND THEIR IMPACT ON THE ECONOMY (British Journal of Global Ecology and Sustainable Development, 2023)
This article presents the reforms in the tax system of the country and their impact on the economy, amendments and additions to the Tax Code of the Republic of Uzbekistan, the expected implementation of the state budget and state trust funds in 2022 and the forecast for 2023.